Mechanisms for Secure Data Transmission: A Survey - Jyoshna, B (International Journal of Computer Sciences and Engineering, 2014)
In today's communications, data transmission play a vital role, but sending data in secure is crucial and important and it should free from unauthorized access. There are various possible techniques like Cryptography, Steganography, and Quantum Cryptography are available for secure transmission of data .This paper discusses some of the mechanisms for secure data transmission securely.